Periodontitis and airflow limitation in older Swedish individuals. (21st April 2020) - Winning, Lewis; Polyzois, Ioannis; Sanmartin Berglund, Johan; Renvert, Stefan
Abstract: Aim: To investigate whether there was an association between periodontitis and airflow limitation in older Swedish individuals. Materials and Methods: Study individuals were randomly selected from the Swedish civil registration database representing the ageing population in Karlskrona, Sweden. Clinical and radiographic examinations were performed, alongside which participants completed questionnaires gathering information on their medical history, social circumstances, demographic background and tobacco use. A physical examination assessed anthropometric measures. Standard spirometry was performed to identify subjects with airflow limitation. Periodontitis was defined based on radiographic periodontal bone loss. Analysis included multiple logistic regression with adjustment for various confounders. Results: A total of 826 Caucasian dentate subjects were included in the analysis. The median age of participants was 73.2 (IQR 66–81) years, and 443 (54.6%) subjects were female. Eighty‐six (10.4%) individuals presented with airflow limitation. The proportion of participants presenting with periodontitis in the airflow limitation group was 65.1% compared to 41.5% with normal respiratory function ( p  < .001). Multiple logistic regression analysis showed that periodontitis was independently associated with airflow limitation with an odds ratio of 2.31 (95% CI 1.27–4.22) p  < .01. Conclusion: In this group of older dentate individuals, periodontitis was significantly associated with airflow limitation independent of other known risk factors.